Queer(ing) Urban Space : Histories, Tactics, Futures in a Glocal World - Albrecht, Jessica,; Sarkar, Sanchali, (Social Sciences E-Books Online, Collection 2026., 2026)
Queer(ing) Urban Space: Histories, Tactics, and Futures in a Glocal World brings together case studies on queerness and queering in urban spaces across diverse global contexts. Engaging with power, narrative, and desire, it responds to calls for new urban epistemologies beyond Western normative frameworks. The volume foregrounds intersections between Global North and South, exploring how colonial legacies, legal regimes, and spatial politics shape queer life. While research on queer access to public space has focused on Western cities, this book highlights underexplored contexts in the Global South, offering critical insights into how queerness challenges, negotiates, and reimagines the cis-heteronormative logics of urban modernity.